Estudo diacrônico da construção V1(chegar) + PREP(a) + V2(infinitivo) no português brasileiro - Elizene Sebastiana de Oliveira Nunes (2014)
In a diachronic perspective, the interface between the theory of linguistic variation and change and grammaticalization, we studied the construction V1CHEGAR + PREPa + V2infinitive in PB. The major objective of this study was to investigate whether the verb chegar grammaticalized itself as an auxiliary one and, having grammaticalized, it began to present aspectual and / or modal functions. The analyses found theoretical support in authors who talk about grammaticalization, such as Lehmann (1982), Hopper (1987, 1991), Hopper and Traugott (1993, 2003), Gonçalves (2007), among others. Furthermore, authors such as Pontes (1973), Lobato (1975), Longo and Campos (2002), Travaglia (1985), Neves (2006), Koch (1995, 2006), Guimarães (1995) and Cabral (2011) subsidized the analyses regarding the verbal condition of being auxiliarityand aspectual and modal marking. Firstly, based on lexicographical consultations and evidences with corpus data, different uses and meanings of chegar in PB were identified, which helped to check the process of abstratization of the item, leading it to grammaticalization. Secondly, the construction V1CHEGAR + PREPa + V2infinitive was subjected to 12 condition of being auxiliarity criteria among authors who study the referred topic, and, of this total, 8 criteria were updated, giving to chegar the status of an auxiliary verb. Then we analyzed the construction in an aspectual classification proposed by Travaglia (1985) and it was evidenced that, from the standpoint of completion, the perfective aspect is predominant in the construction. From the point of view of realization stages, there are terminative contour expressions, which is not enough to state that the item presents that aspect because it behaves distinctly from prototypical auxiliary terminatives such as terminar and acabar. The modal marking was studied based on Neves (2006). Analyzing the construction of argumentation bias, the modality was proven via scale, which also provides chegar with the function of argumentative operator, as, when one schedules events or actions in the enunciations, it gives the staggered event or action a greater argumentative force.